Influence of diverse crop management practices on weed suppression, crop and water productivity and nutrient dynamics in Bt-cotton (Gossypium hirsutum) based intercropping systems in a semi-arid Indo-Gangetic plains region - RAJPOOT, SUDHIR K; RANA, D S; CHOUDHARY, ANIL K (The Indian Journal of Agricultural Sciences, 2016)
Transplanted cotton (Gossypium sp) harnessed significantly highest seed cotton yield (3.22 tonnes/ha), system productivity, IWUE and IWP over direct-seeded cotton besides suppressing weed population. Cotton + cowpea intercropping system also suppressed the weeds and their growth at different growth stages over cotton + okra system and sole cotton. Planting geometry of 90 × 60 cm proved significantly superior over 120 × 45 cm in terms of seed cotton yield, system productivity, IWUE and IWP. Among intercropping systems, sole cotton registered significantly highest seed cotton yield. Total N and P uptake was highest under transplanted cotton while direct seeded cotton revealed higher total K uptake. Cotton + cowpea intercropping system removed highest N and P while cotton + okra exhibited highest K uptake. Transplanted cotton and cotton + cowpea intercropping system led to actual N build up of +8 and +17 kg N/ha, respectively. Similarly, cotton + cowpea and cotton + okra intercropping systems led to actual K balance of –102.1 and –105.4 kg K/ha, respectively. Overall, transplanted Bt-cotton with planting geometry of 90 × 60 cm under cotton + cowpea intercropping system led to highest seed cotton yield, system productivity, less weed infestation and high IWUE and IWP. Transplanted Bt-cotton also led to comparatively +ve N balance and less depletion of P and K as compared to direct seeding in a semi-arid IGPR.